Perencanaan Debit dan Sistem Air Bersih Perumahan Manyar Raya Resort Kecamatan Manyar Kabupaten Gresik - Dandy Nugroho; Bana Ervadius; Titik Suhartatik (Wahana Teknik, 2021)
Water has a very important role in the life of humans and other creatures. Population growth must be followed by the availability of clean and healthy water. This research was conducted at the Manyar Raya Resort Sukomulyo Housing, Manyar District, Gresik Regency. The total population in 2018 was around 400 people, consisting of various ages. The purpose of this study is to: 1) determine the need for clean water for housing until 2025, 2) determine the hydraulic conditions of the pipeline network (pressure, speed, and slope of the hydraulic line), and 3) knowing the analysis of the domestic water demand for Manyar Raya Resort housing. This study uses a quantitative method with an exponential approach. The discharge data and network plan were obtained from the Gresik Regency PDAM office and field observations. The purpose of observation is to collect data, check the location, and collect data. Completion of research calculations with EPANET program tools. The results of this study are: 1) Manyar Raya Resort housing requires 3,925 liters of water/day with a service level of 90%. 2) The hydraulic condition of the clean water velocity is 0.01 – 0.07 m/sec, the pipe water pressure is in the range of 10 – 60 mH2O3, and the slope of the hydraulic line is between 0.02 – 0.14 m/km. 3) The results of the hydraulics analysis, the diameter of the main distribution pipe plan is 100 mm with a roughness coefficient of 120 (fine pipe type), the highest head loss in the pipe is 1.745 meters and the lowest is 0.302 meters, and makes the dimensions of the useful capacity of the tube measuring 2.75 x 2.75 x 3.85 m. Thus, the need for clean water in 2025 can still be met, and the construction of new reservoirs is used when the PDAM water dies and for a long period of time. Keywords: Clean, Debit, Planning, System, Water.